Analisis Akurasi flowrate dan Ketidakpastian Syringe Pump Produk Dalam Negeri dengan Metode ISO GUM - MUHAMMAD AFIFUDIN; Eka Nuryanto Budisusila (LPPM POLBITRADA, 2025)
This study evaluates the accuracy of locally manufactured syringe pumps used in Karanganyar District Hospital and analyzes their measurement uncertainty based on the ISO GUM method. Five Indonesian brands (Endo, Esa Tech, Inmedik, KalTech, and Krisma) were tested using an Infusion Device Analyzer at three flow-rate set-points (10, 50, and 100 ml/h) and an occlusion test at 100 ml/h. All devices met the standard tolerance limits (±10% and <20 psi). The expanded uncertainty ranged from ±0.09 to ±0.70 ml/h, indicating reliable measurement performance. KalTech and Inmedik demonstrated the most stable accuracy, while Esa Tech tended to over-read at low flow rates and Krisma showed significant under-reading at high flow rates, though still within acceptable limits. Statistical tests confirmed no significant differences among brands. Overall, the findings support that Indonesia-made syringe pumps meet technical requirements and strengthen the implementation of the national TKDN policy for reducing dependence on imported medical devices.